Integration of SAR Data Into Monitoring of the 2014–2015 Holuhraun Eruption, Iceland: Contribution of the Icelandic Volcanoes Supersite and the FutureVolc Projects - Dumont, Stéphanie; Sigmundsson, Freysteinn; Parks, Michelle M.; Drouin, Vincent J. P.; Pedersen, Gro B. M.; Jónsdóttir, Ingibjörg; Höskuldsson, Ármann; Hooper, Andrew; Spaans, Karsten; Bagnardi, Marco; Gudmundsson, Magnús T.; Barsotti, Sara; et al. (Frontiers in Earth Science, 2018)
We report how data from satellite and aerial synthetic aperture radar (SAR) observations were integrated into monitoring of the 2014-2015 Holuhraun eruption in the Bárðarbunga volcanic system, the largest effusive eruption in Iceland since the 1783-84 Laki eruption. A lava field formed in one of the most remote areas in Iceland, after the propagation of a ~50 km-long dyke beneath the Vatnajökull ice cap, where the Bárðarbunga caldera is located. Due to the 6 month duration of the eruption, mainly in wintertime, daily monitoring was particularly challenging. During the eruption, the European volcanological project FutureVolc was ongoing, allowing collaboration of many European experts on volcano monitoring activities. Icelandic volcanoes are also a permanent Supersite within the Geohazard Supersites and Natural Laboratories (GSNL) initiative, with support from the Committee on Earth Observation Satellite (CEOS) in the form of a large collection of SAR images. SAR data were acquired by Cosmo-SkyMed (CSK) and TerraSAR-X (TSX) satellites and complemented by aerial SAR images. The large set of SAR satellite data significantly contributed to the daily monitoring during the unrest at Bárðarbunga caldera, the Holuhraun eruption and the year following the eruption. Detection of surface changes using both SAR amplitude and phase information was conducted throughout the whole duration of the volcano-tectonic event, and in the following months, to quantify and track the evolution of volcanic processes at Holuhraun and geothermal activity at Bárðarbunga volcano. Combination of SAR data with other data sets, e.g. satellite optical images and geodetic Global Positioning System (GPS) measurements, was essential for the evaluation of the volcanic hazard in the whole area. International collaboration within the Futurevolc project formed the basis for successful analyses and interpretation of the large SAR data set. Information was provided at Scientific Advisory Board meetings of the Icelandic Civil Protection and used in decision-making, as well as for supporting field-deployment and air-based surveys.